Enhanced impact of early‐summer tropical eastern Pacific sea surface temperature on the July–August precipitation over North China after the late 1970s - Liu Yang; Junhu Zhao; Shuai Li; Naihui Zang; Guolin Feng (International Journal of Climatology, 2022)
This study identified an enhanced interannual relationship between early‐summer (June–July) tropical eastern Pacific (TEP) sea surface temperature (SST) and subsequent mid‐summer (July–August) precipitation in North China (NC) since the late 1970s. For 1951–1972, the relationship between early‐summer TEP SST and mid‐summer NC precipitation were statistically insignificant. In contrast, for 1977–2018, they were positively significant. Since the late 1970s, the early‐summer negative TEP SST anomaly was generally followed by a significant anomalous anticyclone over the Korean Peninsula and its environs; that facilitated anomalous southerly winds over NC, conveying more moisture from the North Pacific, leading more precipitation over NC. Further studies show that the enhanced relationship between early‐summer TEP SST and tropical Indian Ocean to WNP SST are suggested to be responsible for significantly anticyclonic anomalies over WNP after the late 1970s.